2023
DOI: 10.1111/phn.13216
|View full text |Cite
|
Sign up to set email alerts
|

Integrative literature review: Ethylene oxide exposure signs and symptoms

Linda O'Kelley,
Barbara Swanson,
Jessica C. Bishop‐Royse

Abstract: BackgroundAlthough ethylene oxide (EtO) gas is designated as a human carcinogen, extant literature reports mixed findings on the health effects of exposure. The disparate findings may reflect industry bias as many studies were funded by a large chemical industry lobby.ObjectiveTo conduct an integrative review of studies free from industry bias to facilitate compilation of a comprehensive list of reported signs and symptoms of EtO exposure.MethodsWe reviewed 1887 papers of which 42 articles met inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Many articles found no statistically significant findings of exposure effects while others found significantly increased rates of cancer, neurologic symptoms, and respiratory problems. 1 Upon further investigation, it was found that organizations with vested interests in the research outcomes, namely a well-funded lobby and individual chemical-producing companies, funded or sponsored all but one of the articles with no reported significant ill health effects. At the first read, the methods appeared sound.…”
Section: Guest Editorialmentioning
confidence: 99%
“…Many articles found no statistically significant findings of exposure effects while others found significantly increased rates of cancer, neurologic symptoms, and respiratory problems. 1 Upon further investigation, it was found that organizations with vested interests in the research outcomes, namely a well-funded lobby and individual chemical-producing companies, funded or sponsored all but one of the articles with no reported significant ill health effects. At the first read, the methods appeared sound.…”
Section: Guest Editorialmentioning
confidence: 99%
“…Ethylene oxide (EO) is a toxic industrial chemical used in medical device sterilization, plastics and textile manufacturing, and other industrial applications 7 . It forms hemoglobin adducts of EO (HbEO) by binding with hemoglobin (Hb), which serves as a specificity indicator to assess ethylene oxide exposure 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on EtO have primarily focused on its carcinogenicity. Numerous investigations unequivocally established EtO’s carcinogenic properties ( O'Kelley et al, 2023 ), particularly its link to lympho-hematopoietic cancer and breast cancer ( Jinot et al, 2018 ; Marsh et al, 2019 ). As a result, the International Agency for Research on Cancer (IARC) classified EtO as a Group 1 human carcinogen ( Vincent et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%